Lithium ferrite lithium supplement agent and preparation method thereof, positive electrode and lithium ion battery
By combining the sol-gel method and hydrothermal method, nano-sized lithium ferrate lithium supplement agent was prepared, which solved the problem of large size and poor performance of lithium ferrate particles in the prior art, and achieved improvement in the performance of lithium batteries and simplification of process.
Patent Information
- Application Number
- CN202510009465.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, the particle size of synthetic lithium ferrate (Li5FeO4) is relatively large, easily broken, affecting the performance of lithium batteries. In addition, the solid-phase sintering method has problems such as multiple sintering, long sintering time, and high product impurity content.
The nanometer-sized lithium ferrate lithium supplement agent is prepared by combining the sol-gel method with hydrothermal method, through the first mixing treatment, standstill treatment, hydrothermal treatment and sintering treatment, with uniform particle size distribution and high crystallinity.
The prepared lithium nanoferrate lithium supplementation agent improves the performance of lithium-ion batteries, including improving the diffusion rate of lithium ions and the cycle life of the battery, while simplifying the synthesis process and reducing the product impurity content.
Smart Images

Figure CN119764454A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of lithium ion batteries, and in particular to a lithium ferrite supplement and a preparation method thereof, a positive electrode and a lithium ion battery. Background Art
[0002] Lithium ferrite (Li5FeO4), as a lithium-containing compound, can be widely used in the process of battery pre-lithiation. However, the current method for synthesizing Li5FeO4 is mostly solid-phase sintering, and the resulting lithium ferrite particles are large in size, which easily leads to particle breakage and affects the performance of lithium batteries. Furthermore, large particles increase the diffusion distance of lithium ions, which is not conducive to the rapid diffusion of lithium ions. And the solid-phase sintering method often faces the problems of multiple sintering, long sintering time, and high impurity content of the product. In the prior art, the sol-gel method can also be used to prepare the positive electrode lithium supplement material Li5FeO4, but the parameters of the stable intermediate formed by the sol-gel method are relatively harsh, the stability is poor, and the particles formed after sintering are large, which poses a great safety hazard to battery lithium supplementation. Summary of the invention
[0003] The purpose of the present disclosure is to provide a lithium ferrite lithium supplement and a preparation method thereof, a positive electrode and a lithium ion battery. The lithium ferrite lithium supplement has a uniform size and a nanometer size, thereby improving the performance of the lithium ion battery.
[0004] In order to achieve the above-mentioned purpose, the first aspect of the present disclosure provides a lithium ferrite lithium supplement agent, comprising a lithium ferrite core and a carbon coating layer coated on the surface of the lithium ferrite core; the D50 particle size of the lithium ferrite lithium supplement agent is 100-350nm.
[0005] Optionally, the D50 particle size of the lithium ferrite supplement is 100-200 nm; The particle size distribution width SPAN of the lithium ferrite lithium supplement is 0.32-0.62.
[0006] Optionally, the BET specific surface area of the lithium ferrite supplement is 0.32-0.66 m 2 / g, and the crystallinity of the lithium ferrite supplement is 90-98%.
[0007] The second aspect of the present disclosure provides a method for preparing a lithium ferrite lithium supplement, comprising the following steps: S1, performing a first mixing process on an iron source, a lithium source, a complex and a solvent to obtain a raw material mixture; S2, allowing the raw material mixture to stand for a treatment to obtain a wet gel; S3, subjecting the wet gel to hydrothermal treatment to obtain a precursor product; S4, performing a second mixing process on the precursor product and the carbon source, and performing a sintering process; Steps S1-S2 are performed under an inert atmosphere.
[0008] Optionally, in step S1, the molar ratio of the iron source: lithium source: complex is 1: (4-8): (3-6); Based on the total weight of the raw material mixture, the content of the solvent is 66-69% by weight; The pH of the raw material mixture is 2.5-4.5.
[0009] Optionally, in step S1, the iron source is selected from one or more water-soluble salts of iron; the lithium source is selected from one or more water-soluble salts of lithium; the complex is selected from one or more organic acids; and the solvent is selected from one or more water and alcohol.
[0010] Optionally, the iron source includes one or more of Fe(NO3)·9H2O, FeCl3·6H2O and Fe2(SO4)3; The lithium source includes one or more of LiOH·H2O, Li2CO3, LiNO3, LiCH3COO and Li2C2O4; The complex comprises one or more of acetic acid, oxalic acid, citric acid, ethylenediaminetetraacetic acid, ascorbic acid and polyacrylic acid; The solvent includes one or more of water, ethanol, methanol and ethylene glycol.
[0011] Optionally, in step S1, the conditions of the first mixing treatment include: magnetic stirring time of 20-40 min, stirring temperature of 22-28° C., and stirring speed of 150-600 rpm.
[0012] Optionally, in step S2, the conditions for the static treatment include: a static temperature of 22-28° C. and a static time of 16-30 h.
[0013] Optionally, in step S3, the conditions of the hydrothermal treatment include: the hydrothermal temperature is 80-220° C., and the hydrothermal time is 4-20 h.
[0014] Optionally, in step S4, the carbon source is selected from one or more of glucose, sucrose and sodium gluconate; The weight ratio of the precursor product to the carbon source is 90-110:1.
[0015] Optionally, in step S4, the sintering process includes a first sintering process and a second sintering process performed sequentially; The conditions of the first sintering treatment include: heating to 400-800° C. at a first heating rate in an air atmosphere, and sintering time is 3-6 hours; the first heating rate is 5-15° C. / min; The conditions of the second sintering treatment include: heating to 600-1000° C. at a second heating rate under an inert atmosphere, and sintering time is 5-8 hours; the second heating rate is 5-15° C. / min.
[0016] A third aspect of the present disclosure provides a lithium ferrite lithium supplement prepared according to the method described in the second aspect of the present disclosure.
[0017] A fourth aspect of the present disclosure provides a positive electrode, comprising the lithium ferrite lithium supplement agent described in the first aspect or the third aspect of the present disclosure.
[0018] A fifth aspect of the present disclosure provides a lithium-ion battery, comprising the positive electrode described in the fourth aspect of the present disclosure.
[0019] Through the above technical scheme, the present disclosure provides a lithium ferrite lithium supplement and its preparation method, positive electrode and lithium ion battery. The lithium ferrite lithium supplement has a nanometer size, increases the reaction interface and can provide more diffusion channels; and the uniform and smaller nanoparticles shorten the diffusion length of lithium ions and increase the diffusion rate of lithium ions. The present disclosure adopts a sol-gel method combined with a hydrothermal method, and can prepare a nano lithium ferrite lithium supplement by first nucleating and then controlling the crystal growth rate. Compared with the method of directly drying the sol or directly using a hydrothermal method to prepare a gel, the present disclosure is useful for generating a stable wet gel by standing in an inert gas environment; because the growth of particles is suppressed during the sol-gel reaction, the crystal growth rate is slower, the obtained particle size is often smaller and the particle size distribution is more uniform, and the crystallinity is higher, the particle structure stability is better, and the cycle life in battery applications is also higher; the preparation method provided by the present disclosure can also avoid multiple sintering (≥3 times), the synthesis process is simpler, and the impurity content of the obtained product is lower. The lithium ferrite lithium supplement provided by the present disclosure is applied to lithium ion batteries, which can effectively improve the efficiency and service life of the battery.
[0020] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings: Figure 1 This is a SEM electron microscope photo of the product obtained in Example 1 of the present disclosure; Figure 2 This is a SEM electron microscope photograph of the product obtained in Comparative Example 1 of the present disclosure; Figure 3 The XRD spectra of the products obtained in Example 1 and Comparative Example 1 of the present disclosure; Figure 4 This is a test chart of the cycle performance of the products obtained in Example 1 and Comparative Example 1 of the present disclosure in lithium-ion battery applications. DETAILED DESCRIPTION
[0022] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0023] The first aspect of the present disclosure provides a lithium ferrite lithium supplement, comprising a lithium ferrite core and a carbon coating layer coated on the surface of the lithium ferrite core; the D50 particle size of the lithium ferrite lithium supplement is 100-350nm.
[0024] The present disclosure provides a lithium ferrite lithium supplement agent, which has a nanometer size, increases the reaction interface, and can also provide more diffusion channels; and the uniform, smaller-sized nanoparticles shorten the diffusion length of lithium ions and increase the lithium ion diffusion rate. The lithium ferrite lithium supplement agent provided by the present disclosure is applied to lithium-ion batteries, which can effectively improve the efficiency and life of the battery.
[0025] In a preferred embodiment, the D50 particle size of the lithium ferrite supplement is 100-200 nm. When the D50 particle size of the lithium ferrite supplement is within the preferred range provided in this embodiment, the lithium ferrite supplement has better lithium ion diffusion properties and can further improve the efficiency and life of the lithium ion battery.
[0026] In a preferred embodiment, the particle size distribution width SPAN of the lithium ferrite lithium supplement is 0.32-0.62, preferably 0.32-0.40. The lithium ferrite lithium supplement provided by the present disclosure has a narrow particle size distribution width. When the SPAN of the lithium ferrite lithium supplement is within the range of the present embodiment, especially within the preferred range, the particle size of the lithium ferrite lithium supplement is more uniform, the properties of the lithium supplement are more stable, and the first coulombic efficiency of the battery is higher and the cycle stability is better in battery applications. The particle size distribution width SPAN is tested and calculated according to the conventional method of the present disclosure.
[0027] In one embodiment, the BET specific surface area of the lithium ferrite supplement is 0.32-0.66 m 2 / g, preferably 0.32-0.43m 2 / g, the crystallinity of the lithium ferrite supplement is 90-98%, preferably 97-98%. The lithium ferrite supplement provided by the present disclosure has a large BET specific surface area and a high crystallinity, and can have a higher first coulombic efficiency and cycle stability in battery applications.
[0028] The second aspect of the present disclosure provides a method for preparing a lithium ferrite lithium supplement, comprising the following steps: S1, performing a first mixing process on an iron source, a lithium source, a complex and a solvent to obtain a raw material mixture; S2, allowing the raw material mixture to stand for a treatment to obtain a wet gel; S3, subjecting the wet gel to hydrothermal treatment to obtain a precursor product; S4, performing a second mixing process on the precursor product and the carbon source, and performing a sintering process; Steps S1-S2 are performed under an inert atmosphere.
[0029] The present disclosure provides a method for preparing a lithium ferrite lithium supplement. The present disclosure adopts a sol-gel method combined with a hydrothermal method, and can prepare a nano lithium ferrite lithium supplement by first nucleating and then controlling the crystal growth rate. Compared with a method of directly drying the obtained sol or directly adopting a hydrothermal method to prepare a gel, the present disclosure is conducive to the generation of a stable wet gel by static treatment in an inert gas environment; since the growth of particles is suppressed during the sol-gel reaction, the crystal growth rate is slower, the obtained particle size is often smaller and the particle size distribution is more uniform, and the crystallinity is higher, the particle structure stability is better, and the cycle life is longer; the preparation method provided by the present disclosure can also avoid multiple sintering, the synthesis process is simpler, and the obtained product has a lower impurity content.
[0030] In a specific embodiment, the inert atmosphere is selected from one or more of nitrogen and argon.
[0031] In one embodiment, in step S1, the molar ratio of the iron source: the lithium source: the complex is 1: (4-8): (3-6); preferably 1: (5-6): (4-5); according to the molar ratio of the raw materials in this embodiment, especially according to the preferred molar ratio, a lithium ferrite supplement with better performance can be prepared.
[0032] In a specific embodiment, in step S1, the content of the solvent is 66-69% by weight based on the total weight of the raw material mixture; optionally, the amount of the solvent added is 200-210 g. Adding the solvent according to the content in this embodiment is conducive to regulating the crystal growth rate by accurately controlling the precursor concentration, thereby obtaining smaller nanoparticles.
[0033] In a preferred embodiment, the pH of the raw material mixture is 2.5-4.5, preferably 3-3.5. Controlling the pH value of the raw material mixture within the range of this embodiment can effectively prevent the hydrolysis of the iron source, thereby improving the performance of the lithium ferrite supplement.
[0034] In one embodiment, in step S1, the iron source is selected from one or more water-soluble salts of iron; the lithium source is selected from one or more water-soluble salts of lithium; the complex is selected from one or more organic acids; and the solvent is selected from one or more water and alcohol.
[0035] In a specific embodiment, in step S1, the iron source includes one or more of Fe(NO3)·9H2O, FeCl3·6H2O and Fe2(SO4)3; The lithium source includes one or more of LiOH·H2O, Li2CO3, LiNO3, LiCH3COO and Li2C2O4; The complex comprises one or more of acetic acid, oxalic acid, citric acid, ethylenediaminetetraacetic acid, ascorbic acid and polyacrylic acid; The solvent includes one or more of water, ethanol, methanol and ethylene glycol.
[0036] The reagents used in the present disclosure can be purchased through commercial channels or prepared by known methods.
[0037] In one embodiment, in step S1, the conditions of the first mixing treatment include: magnetic stirring time of 20-40 min, stirring temperature of 22-28° C., and stirring speed of 150-600 rpm; preferably, the magnetic stirring time is 25-30 min, the stirring temperature is 24-26° C., and the stirring speed is 250-350 rpm; performing the first mixing treatment according to the conditions in this embodiment can improve the dispersion uniformity of the raw materials.
[0038] In one embodiment, in step S2, the conditions for the static treatment include: a static temperature of 22-28° C. and a static time of 16-30 hours; preferably, a static temperature of 23-26° C. and a static time of 20-24 hours. According to the conditions in this embodiment, especially according to the preferred conditions, a more stable wet gel can be obtained, and the crystallinity of the final product can be improved.
[0039] In one embodiment, in step S3, the conditions of the hydrothermal treatment include: a hydrothermal temperature of 80-220°C, a hydrothermal time of 4-20 hours, and a hydrothermal pressure of the autogenous pressure in the hydrothermal reaction device; preferably, the hydrothermal temperature is 150-200°C, the hydrothermal time is 10-15 hours, and the hydrothermal reaction device used in the present disclosure can be a sealed Teflon-lined stainless steel autoclave. According to the hydrothermal conditions in this embodiment, especially according to the preferred conditions, the hydrothermal reaction can promote the reaction and reduce the occurrence of side reactions.
[0040] In a specific embodiment, step S3 further includes: subjecting the hydrothermal treatment product to solid-liquid separation, and subjecting the solid product to washing and vacuum drying. Optionally, the vacuum drying conditions include: a vacuum drying temperature of 80-150° C. and a drying time of 8-14 h.
[0041] In one embodiment, in step S4, the carbon source is selected from one or more of glucose, sucrose and sodium gluconate; the carbon source type provided by this embodiment can have a better carbon coating effect.
[0042] In a preferred embodiment, the weight ratio of the precursor product to the carbon source is 90-110:1, preferably 95-105:1, which is beneficial to improving the carbon coating effect and the performance of the lithium ferrite supplement product.
[0043] In one embodiment, in step S4, the sintering process includes a first sintering process and a second sintering process performed sequentially; The conditions of the first sintering treatment include: heating to 400-800° C. at a first heating rate in an air atmosphere, and sintering time is 3-6 hours; the first heating rate is 5-15° C. / min; The second sintering treatment conditions include: heating to 600-1000°C at a second heating rate under an inert atmosphere, and sintering time is 5-8h; the second heating rate is 5-15°C / min. According to the conditions in this embodiment, a lithium ferrite supplement with better performance can be prepared.
[0044] A third aspect of the present disclosure provides a lithium ferrite lithium supplement prepared according to the method described in the second aspect of the present disclosure.
[0045] A fourth aspect of the present disclosure provides a positive electrode, comprising the lithium ferrite lithium supplement agent described in the first aspect or the third aspect of the present disclosure.
[0046] In a specific embodiment, the positive electrode includes a positive electrode coating, and the positive electrode coating includes a positive electrode active material, a positive electrode conductive agent, a positive electrode binder and the lithium ferrite lithium supplement; Based on the total weight of the positive electrode coating, the content of the positive electrode active material is 90-94% by weight, the content of the positive electrode conductor is 2-3% by weight, the content of the positive electrode binder is 2-3% by weight, and the content of the lithium ferrite lithium supplement is 2.4-3.2% by weight; preferably, the content of the positive electrode active material is 92.15% by weight, the content of the positive electrode conductor is 2.5% by weight, the content of the positive electrode binder is 2.5% by weight, and the content of the lithium ferrite lithium supplement is 2.85% by weight; when the positive electrode coating has the composition provided in this embodiment, the lithium ion battery can have better performance.
[0047] In a specific embodiment, in the positive electrode coating, the amount of the positive electrode active material is 45-47g, the amount of the positive electrode conductive agent is 1-1.5g, the amount of the positive electrode binder is 1-1.5g, and the amount of the lithium ferrite lithium supplement is 1.2-1.6g; preferably, the amount of the positive electrode active material is 46.08g, the amount of the positive electrode conductive agent is 1.25g, the amount of the positive electrode binder is 1.25g, and the amount of the lithium ferrite lithium supplement is 1.42g. When the amount of the components in the positive electrode coating is within the range of this embodiment, it helps to improve the performance of the lithium ion battery.
[0048] In the present disclosure, the positive electrode active material, positive electrode conductive agent, and positive electrode binder can be selected from the conventional types in the art, for example, the positive electrode active material can be selected from one or more of lithium iron phosphate and ternary materials; the positive electrode conductive agent can be selected from one or more of conductive carbon black, carbon nanotubes, and conductive polymers; the positive electrode binder can be selected from one or more of polyvinylidene fluoride and polyvinyl alcohol. The positive electrode coating can be obtained by conventional slurry coating.
[0049] A fifth aspect of the present disclosure provides a lithium-ion battery, comprising the positive electrode described in the fourth aspect of the present disclosure.
[0050] In the present disclosure, the lithium-ion battery also includes a negative electrode, an electrolyte, and a separator, etc., which can be of the types conventionally selected in the art. For example, the negative electrode includes a negative electrode coating, and the negative electrode coating can include a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder, wherein the negative electrode active material is selected from one or more of graphite and hard carbon; the negative electrode conductive agent can be selected from one or more of conductive carbon black, carbon nanotubes, and graphene; the negative electrode binder can be selected from one or more of CMC (sodium carboxymethyl cellulose), SBR (styrene butadiene rubber), and PAA (polyacrylic acid). The negative electrode coating can be obtained by conventional slurry coating. The electrolyte can be selected from lithium iron phosphate electrolyte. The separator can be an ion exchange membrane, etc.
[0051] The present disclosure is further described in detail below through examples. The raw materials used in the examples can all be obtained through commercial channels.
[0052] The microscopic morphology of the samples was tested using a HITACHI SU8600 scanning electron microscope (SEM) tester; The XRD test spectrum of the sample was obtained by using the PANalytical Empyrean X-ray powder diffractometer of the Netherlands. The test conditions included: using Cu Kα as the radiation source and the test range was 10-90°; The particle size distribution of the samples was statistically obtained using Nanomeasurer software; The D50 particle size of the sample was obtained using the American Brookhaven NanoBrook 90Plus Zeta test.
[0053] Example 1 Take 0.10 mol FeCl3·6H2O (iron source) and citric acid (complex) and dissolve them in a mixed solvent of 48 mL distilled water and 72 mL ethanol, ensure that the pH value of the solution is about 3.5, and stir for 10 min under N2 atmosphere at room temperature (25°C). Use a syringe pump to slowly drip 5 mol / L LiCH3COO·2H2O (lithium source) solution into the above solution at a rate of 1 drop per minute, so that the amount of LiCH3COO·2H2O added is 0.50 mol, and continue to stir under this condition for 30 minutes (first mixing treatment) to obtain a raw material mixture, in which the molar ratio of iron source: lithium source: complex is 1:5:5, and the content of the solvent is 63% by weight based on the total weight of the raw material mixture.
[0054] The resulting solution (raw material mixture) was allowed to stand for 24 h (standing treatment) under N2 atmosphere at room temperature (25°C). This process helped to stabilize the formation of the gel and obtain a wet gel.
[0055] The wet gel was then placed in a Teflon-lined stainless steel autoclave and heated at 190 °C for 12 h (hydrothermal treatment). After the reaction was completed, the solution was dried in a vacuum drying oven for 10 h with the oven temperature controlled at 120 °C to obtain a precursor product.
[0056] The dried precursor product is then mixed with glucose (carbon source) with a mass concentration of 17 wt %, wherein the weight ratio of the precursor product to the carbon source (effective weight in the carbon source solution) is 100:1; and then sintering treatments are performed in sequence, and the sintering treatment conditions include: keeping warm at 600 ° C in an air atmosphere for 6 h (first sintering treatment), a first heating rate of 10 ° C / min, and then keeping warm at 900 ° C in an argon atmosphere for 5 h (second sintering treatment), and a second heating rate of 10 ° C / min, to obtain nano Li5FeO4 with high crystallinity and uniform particle size.
[0057] Example 2 This example refers to the preparation method in Example 1, and the difference from Example 1 is that: The standing treatment time is 16 hours; the rest of the process is the same as in Example 1, and nano-Li5FeO4 with high crystallinity and uniform particle size is prepared.
[0058] Example 3 This example refers to the preparation method in Example 1, and the difference from Example 1 is that: The standing treatment time is 30 hours; the rest of the process is the same as in Example 1, and nano-Li5FeO4 with high crystallinity and uniform particle size is prepared.
[0059] Example 4 This example refers to the preparation method in Example 1, and the difference from Example 1 is that: The standing treatment time is 12 hours; the rest of the process is the same as in Example 1, and Li5FeO4 is prepared.
[0060] Example 5 This example refers to the preparation method in Example 1, and the difference from Example 1 is that: The standing treatment time is 40 hours; the rest of the process is the same as in Example 1, and Li5FeO4 is prepared.
[0061] Example 6 This example refers to the preparation method in Example 1, and the difference from Example 1 is that: The molar ratio of iron source: lithium source: complex is 1:4:3, and the rest of the process is the same as in Example 1 to prepare Li5FeO4.
[0062] Example 7 This example refers to the preparation method in Example 1, and the difference from Example 1 is that: The molar ratio of iron source: lithium source: complex is 1:8:6, and the rest of the process is the same as in Example 1 to prepare Li5FeO4.
[0063] Example 8 This example refers to the preparation method in Example 1, and the difference from Example 1 is that: The molar ratio of iron source: lithium source: complex is 1:2:7, and the rest of the process is the same as in Example 1 to prepare Li5FeO4.
[0064] Comparative Example 1 This comparative example refers to the preparation method in Example 1, and the difference from Preparation Example 1 is that the raw material mixture obtained by the first mixing treatment is directly subjected to hydrothermal treatment without being subjected to static treatment; the remaining process is the same as Example 1, and the prepared Li5FeO4 lithium supplement is obtained.
[0065] The particle size and other data of the lithium ferrite lithium supplement obtained in the above examples and comparative examples are listed in the following Table 1.
[0066] Table 1
[0067] Test Example 1 The morphology of the solid powders obtained in Example 1 and Comparative Example 1 was characterized by scanning electron microscopy (SEM). The characterization results are as follows: Figure 1-Figure 2 As shown. Figure 1 It can be seen that the particle size of the lithium ferrite supplement prepared by the method provided by the present disclosure in Example 1 is uniform. Through the statistical results of the particle size distribution statistical software and the D50 particle size test results, it can be seen that the D50 particle size of the lithium ferrite supplement in Example 1 is in the range of 100-200 nm; the lithium ferrite supplement obtained in Example 1 has achieved a leap from microns to nanometers in size compared to the lithium ferrite (D50≈10μm) particles obtained by the traditional mechanical grinding and solid phase sintering method; and from the frequency distribution histogram, it can be seen that the nanoparticles obtained by this method are uniform in size, with a narrow particle size distribution, and the calculated SPAN is lower, only 0.32. In contrast, the particle size D50 obtained in Comparative Example 1 without static treatment is 100-350 nm. Since the obtained solution is not statically treated under N2 atmosphere at room temperature during preparation, the precursor does not form a stable gel, and the obtained particle size distribution is larger, and the SPAN of the particles obtained in Comparative Example 1 is higher.
[0068] Test Example 2 The solid powders obtained in Example 1 and Comparative Example 1 were characterized by X-ray powder diffractometer. The characterization results were as follows: Figure 3 As shown. Figure 3 It can be seen that the diffraction peak of the powder material obtained in Example 1 matches the diffraction peak of the Li5FeO4 standard PDF card, indicating that Li5FeO4 with high purity is obtained, and the diffraction peak is sharp, indicating that the obtained material has high crystallinity. The diffraction peak intensity of Li5FeO4 obtained in Comparative Example 1 is significantly reduced, indicating that its crystallinity is significantly reduced compared with Example 1, and the material structure with higher crystallinity is often more stable, and thus its cycle performance is better.
[0069] Test Example 3 This test example is used to illustrate the effects of the products obtained in the above embodiments and comparative examples in lithium ion battery applications.
[0070] The positive electrode formula ratio is lithium iron phosphate (positive electrode active material): lithium supplement: conductive carbon black (positive electrode conductive agent): CNT conductive slurry (positive electrode conductive agent): polyvinylidene fluoride (positive electrode binder) = 92.15: 2.85: 2: 0.5: 2.5, the solid content is 57 ± 2% by weight, the viscosity is 4500 ± 1000 mPa·s, and the coating surface density is 160 ± 5 g / m 2 , compacted density is 2.5±0.05g / cm 3The negative electrode formula ratio is graphite (negative electrode active material): conductive carbon black (negative electrode conductive agent): CMC (negative electrode binder): SBR (negative electrode binder) = 95.4:1.2:1.4:2, the solid content is 53±2%, the viscosity is 3000±1000mPa·s, and the coating surface density is 80±2g / m 2 , compacted density is 1.5±0.05g / cm 3 The diaphragm is an ion exchange membrane, and the electrolyte is a conventional lithium iron phosphate electrolyte. The coated electrode is first rolled, then cut, the positive electrode is welded with an aluminum tab, the negative electrode is welded with a copper tab, and then the battery cell is obtained by laminating, assembling, baking, injecting, aging, forming, aging, dividing the capacity, and welding the cap.
[0071] The battery cells prepared with the examples and comparative examples as lithium supplements were also measured for room temperature cycle life. The measurement method was as follows: at room temperature 25±3°C, they were placed for 10 minutes, and charged at a constant power of 0.5CP to a cut-off voltage of 3.65V. After charging, they were placed for 10 minutes, and then discharged at a constant power of 0.5CP to 2V. The above steps were repeated for cycle testing.
[0072] The test results are listed in Table 2 below.
[0073] Table 2
[0074] The test results of the lithium supplement agent obtained in Example 1 and Comparative Example 1 in the lithium ion battery cycle performance test are as follows: Figure 4 As shown, it can be seen from the test results that the capacity retention rate of the battery prepared by Example 1 as a lithium supplement is significantly higher than that of the battery prepared by Comparative Example 1. When the number of cycles reaches 2000, the capacity retention rate of the battery prepared by Example 1 as a lithium supplement is higher than that of the battery prepared by Comparative Example 1.
[0075] According to the data in Table 2, we can see that: Compared with the Li5FeO4 lithium supplement prepared in Comparative Example 1 (without static treatment), the Li5FeO4 lithium supplement prepared in Examples 1-8 according to the method provided in the present disclosure can achieve higher first coulombic efficiency and cycle capacity retention rate in lithium-ion batteries.
[0076] Comparing Example 2-3 with Example 4-5, in the process of preparing the lithium supplement agent in Example 2-3, the static treatment is carried out according to the optimized time range (16-30h) provided by the present disclosure, and the static treatment time of Example 4-5 is not within the optimized range. Compared with the lithium supplement agent prepared in Example 4-5, the first coulombic efficiency and cycle capacity retention rate of the Li5FeO4 lithium supplement agent obtained in Example 2-3 in the lithium ion battery are higher; Further comparing Example 1 with Examples 2-3, the static treatment time in Example 1 is within the further preferred range provided in the present disclosure (20-24h), and compared with the lithium supplement obtained in Examples 2-3, the first coulombic efficiency and cycle capacity retention rate of the Li5FeO4 lithium supplement in the lithium ion battery in Example 1 are higher; Comparing Example 6-7 with Example 8, in the lithium supplement preparation process of Example 6-7, the molar ratio of iron source: lithium source: complex is within the optimized range provided by the present disclosure (1:4-8:3-6), while the molar ratio in Example 8 is not within the optimized range. The Li5FeO4 lithium supplement obtained in Example 6-7 has higher first coulombic efficiency and cycle capacity retention rate in lithium ion batteries; Further comparing Examples 6-7 with Example 1, the molar ratio of the raw materials in Example 1 is within the further preferred range provided in the present disclosure (1:5-6:4-5), and the Li5FeO4 lithium supplement obtained in Example 1 has higher first coulombic efficiency and cycle capacity retention rate in lithium-ion batteries.
[0077] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0078] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0079] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A lithium ferrite lithium supplement, characterized in that: It comprises a lithium ferrite core and a carbon coating layer coated on the surface of the lithium ferrite core; the D50 particle size of the lithium ferrite lithium supplement is 100-350nm.
2. The lithium ferrite supplement according to claim 1, characterized in that: The D50 particle size of the lithium ferrite supplement is 100-200 nm; The particle size distribution width SPAN of the lithium ferrite lithium supplement is 0.32-0.
62.
3. The lithium ferrite supplement according to claim 1, characterized in that: The BET specific surface area of the lithium ferrite supplement is 0.32-0.66 m 2 / g, and the crystallinity of the lithium ferrite supplement is 90-98%.
4. A method for preparing a lithium ferrite lithium supplement, characterized in that: The following steps are involved: S1, performing a first mixing process on an iron source, a lithium source, a complex and a solvent to obtain a raw material mixture; S2, allowing the raw material mixture to stand for a treatment to obtain a wet gel; S3, subjecting the wet gel to hydrothermal treatment to obtain a precursor product; S4, performing a second mixing process on the precursor product and the carbon source, and performing a sintering process; Steps S1-S2 are performed under an inert atmosphere.
5. The method according to claim 4, characterized in that In step S1, the molar ratio of the iron source: lithium source: complex is 1: (4-8): (3-6); Based on the total weight of the raw material mixture, the content of the solvent is 66-69% by weight; The pH of the raw material mixture is 2.5-4.
5.
6. The method according to claim 4, characterized in that In step S1, the iron source is selected from one or more water-soluble salts of iron; the lithium source is selected from one or more water-soluble salts of lithium; the complex is selected from one or more organic acids; and the solvent is selected from one or more water and alcohol.
7. The method according to claim 6, characterized in that The iron source includes one or more of Fe(NO3)·9H2O, FeCl3·6H2O and Fe2(SO4)3; The lithium source includes one or more of LiOH·H2O, Li2CO3, LiNO3, LiCH3COO and Li2C2O4; The complex comprises one or more of acetic acid, oxalic acid, citric acid, ethylenediaminetetraacetic acid, ascorbic acid and polyacrylic acid; The solvent includes one or more of water, ethanol, methanol and ethylene glycol.
8. The method according to claim 4, characterized in that In step S1, the conditions of the first mixing treatment include: magnetic stirring time of 20-40 min, stirring temperature of 22-28° C., and stirring speed of 150-600 rpm.
9. The method according to claim 4, characterized in that In step S2, the conditions for the static treatment include: a static temperature of 22-28°C and a static time of 16-30h.
10. The method according to claim 4, characterized in that In step S3, the conditions of the hydrothermal treatment include: the hydrothermal temperature is 80-220° C., and the hydrothermal time is 4-20 h.
11. The method according to claim 4, characterized in that In step S4, the carbon source is selected from one or more of glucose, sucrose and sodium gluconate; The weight ratio of the precursor product to the carbon source is 90-110:
1.
12. The method according to claim 4, characterized in that In step S4, the sintering process includes a first sintering process and a second sintering process performed sequentially; The conditions of the first sintering treatment include: heating to 400-800° C. at a first heating rate in an air atmosphere, and sintering time is 3-6 hours; the first heating rate is 5-15° C. / min; The conditions of the second sintering treatment include: heating to 600-1000° C. at a second heating rate under an inert atmosphere, and sintering time is 5-8 hours; the second heating rate is 5-15° C. / min.
13. The lithium ferrite supplement prepared according to the method of any one of claims 4 to 12.
14. A positive electrode, characterized in that: The invention relates to a lithium ferrite supplement comprising the lithium ferrite supplement as described in any one of claims 1 to 3 and 13.
15. A lithium ion battery, characterized in that: Comprising the positive electrode as claimed in claim 14.
Citation Information
Patent Citations
Battery diaphragm and lithium ion battery
CN110197887A
Preparation method of lithium ferrite
CN112117433A
Lithium supplement agent suitable for high-voltage positive electrode as well as preparation method and application of lithium supplement agent
CN115863797A
Positive electrode lithium supplement additive, preparation method thereof and lithium ion battery
CN117865226A
Core-shell structure lithium-ion battery positive electrode material, preparation method thereof, positive electrode plate, lithium-ion battery and application thereof
WO2021037267A1
Cited By
Preparation method and targeting application of morphology-controllable MgFe2O4 catalyst
CN122098579A